Tumor necrosis factor is a necroptosis-associated alarmin - Pinci, Francesca; Gaidt, Moritz M.; Jung, Christophe; Nagl, Dennis; Kuut, Gunnar; Hornung, Veit (Frontiers in Immunology, 2022)
Necroptosis is a form of regulated cell death that can occur downstream of several immune pathways. While previous studies have shown that dysregulated necroptosis leads to strong inflammatory responses, little is known about the identity of the endogenous molecules that trigger necroptosis-mediated inflammatory responses. Using a reductionist in vitro model, we found that soluble TNF is strongly released in the context of necroptosis. On the one hand, necroptosis promotes TNF translation by inhibiting negative regulatory mechanisms acting at the post-transcriptional level. On the other hand, necroptosis markedly enhances TNF release by activating ADAM proteases. In studying TNF release at single-cell resolution, we found that TNF release triggered by necroptosis is activated in a switch-like manner and exceeds steady-state TNF processing in magnitude and speed. Although this shedding response precedes massive membrane damage, it is closely associated with lytic cell death. In fact, we found that lytic cell death induction using a pore-forming toxin also triggers TNF shedding, indicating that the activation of ADAM proteases is not strictly related to the necroptotic pathway but associated with biophysical changes of the cell membrane upon lytic cell death. These results demonstrate that lytic cell death, particularly necroptosis, is a critical trigger for TNF release and thus qualify TNF as a necroptosis-associated alarmin.